2022
DOI: 10.1111/1751-7915.14197
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate limitation as crucial factor to enhance yeast lipid production from short‐chain fatty acids

Abstract: Microbial lipids for chemical synthesis are commonly obtained from sugar‐based substrates which in most cases is not economically viable. As a low‐cost carbon source, short‐chain fatty acids (SCFAs) that can be obtained from food wastes offer an interesting alternative for achieving an affordable lipid production process. In this study, SCFAs were employed to accumulate lipids using Yarrowia lipolytica ACA DC 50109. For this purpose, different amounts of SCFAs, sulfate, phosphate and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Agreeing with previous reports in which hydrodynamic cavitation was applied as pretreatment of livestock wastewater [ 29 ], struvite formation resulted in a marked decrease in phosphorous (50% removal). This phosphorous removal also gave rise to an increase in C:P ratio that has been recently proven to be a promising strategy for improve lipid production [ 30 , 31 ]. Yeast was not affected by any other potential by-products released in the treatment and no additional clearance steps would be required for its application.…”
Section: Resultsmentioning
confidence: 99%
“…Agreeing with previous reports in which hydrodynamic cavitation was applied as pretreatment of livestock wastewater [ 29 ], struvite formation resulted in a marked decrease in phosphorous (50% removal). This phosphorous removal also gave rise to an increase in C:P ratio that has been recently proven to be a promising strategy for improve lipid production [ 30 , 31 ]. Yeast was not affected by any other potential by-products released in the treatment and no additional clearance steps would be required for its application.…”
Section: Resultsmentioning
confidence: 99%
“…The production of second, third, and fourth-generation biodiesel involves the use of oleaginous microorganisms that must accumulate between 20% and 70% of the lipid content in their dry weight [10,20,21]. These microorganisms include certain species of bacteria, algae, and fungi [22].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figures 1 and 2, the most widely used yeasts from the Ascomycota Phylum include Yarrowia lipolytica, Lipomyces starkeyi, Saccharomyces pastorianus, Candida tropicalis, and Metschnikowia pulcherrima. From the Basidiomycota Phylum, species such as Cutaneotrichosporon sp., Rhodotorula sp., Naganishia albida, Phenoliferia glacialis, and Sporobolomyces shibatanus [15,18,19,21,24,26,27,32,35,. All the yeasts reported in Figures 1 and 2 can produce intracellular lipids through the degradation of various substrates used as carbon sources and generate these compounds in different proportions.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported lipid accumulation in yeasts [11,13,14] with the most promising species for fat production being the following: Rhodosporidium toruloides, Lipomyces starkeyi, Lipomyces tetrasporus, Cutaneotrichosporon curvatum, Candida diddensiae, Metschnikowia reukaufii, Candida tropicalis, Solicoccosyma terricola, Naganishia albida, Papiliotrema laurentii, Rhodotorula glutinis, Rhodotorula graminis, Rhodotorula mucilaginosa, Apiotrichum domesticum, Trichosporon asahii, Tausonia pullulans, Yarrowia lipolytica and Schwanniomyces etchellsii [15][16][17][18][19]. Most of these yeasts accumulate lipids mainly in the cytoplasmic membrane (about 25% of the cell dry weight) in the form of triglycerides (TGs) [20], noting that the major production of these TGs is under conditions of nutrient limitation such as nitrogen, phosphorus and an excess carbon source [21][22][23].…”
Section: Introductionmentioning
confidence: 99%